Cultural Secrecy and Anti‐corruption Disclosure in Large Multinational Companies. Issue 2 (10th May 2018) - Blanc, Renata; Branco, Manuel Castelo; Patten, Dennis M.
Abstract: This paper analyses the relation between countries' cultural characteristics and anti‐corruption disclosure. In particular, it extends prior research and examines whether country‐level secrecy also appears to impact differences in this type of disclosure, while controlling for factors previously shown to matter. Using Transparency International ratings of disclosures on anti‐corruption efforts by large multinational firms and an ordinal regression analysis, the paper documents that companies from more 'secretive' countries have significantly lower levels of anti‐corruption disclosure. Abstract : This paper analyses the relation between countries' cultural characteristics and anti‐corruption disclosure. In particular, it extends prior research and examines whether country‐level secrecy also appears to impact differences in this type of disclosure, while controlling for factors previously shown to matter.